Inside Back Cover: An Organoruthenium Anticancer Agent Shows Unexpected Target Selectivity For Plectin (Angew. Chem. Int. Ed. 28/2017). Issue 28 (29th May 2017) - Meier, Samuel M.; Kreutz, Dominique; Winter, Lilli; Klose, Matthias H. M.; Cseh, Klaudia; Weiss, Tamara; Bileck, Andrea; Alte, Beatrix; Mader, Johanna C.; Jana, Samir; Chatterjee, Annesha; Bhattacharyya, Arindam; et al.
Abstract : Metal‐based anticancer agents are often designed as prodrugs with supposedly low selectivity. In contrast to this approach, in their Communication onpage 8267 ff., S. M. Meier, C. Gerner, and co‐workers describe an unexpected target selectivity of an organometallic ruthenium(II) complex, obtained by a combination of proteomics‐based methods, termed target‐response profiling. Plectin was identified as the main cellular target. Plectin‐targeting interferes with the microtubule network and thus may be harnessed as an anticancer strategy.